Analisis Nilai Anthropometri Dan Malnutrisi Pada Laki-Laki Dan Perempuan Usia 17-22 Tahun: Suatu Studi Cross-Sectional - Yusni, Yusni; Yusuf, Hanifah; Murzalina, Cut; Rahman, Safrizal (Majalah Kedokteran Indonesia, 2024)
Introduction: Malnutrition is a worldwide problem that has yet to be resolved, and its prevalence in Indonesia has increased in tandem with changes in people’s lifestyles. Method: This study aims to determine nutritional status based on anthropometric values and investigate malnutrition in male and female aged 17–22 years. The research was conducted using a cross-sectional study. The subjects were male and female, aged 17–22 years, and healthy, with a total of 1,669 male (n=210) and female (n=1459). A questionnaire was used to obtain data. The data was analyzed using a chi-square test (p less than 0.05) and an independent sample t-test (p less than 0.05). Result: Malnutrition was found in subjects who were underweight (male=28.10% and female=26.39%), overweight (male=8.10% and female=9.32%), and obese (male=8.57% and female=6.85%). Total malnutrition in male and female was 27.25% underweight, 8.71% overweight, and 7.71% obese. Nutritional status was not related to gender (p greater than 0.05): underweight (p=0.74), normo-weight (p=0.48), overweight (p=0.34), and obesity (p=0.74). Conclusion: The double burden of malnutrition in males and females aged 17-22 years in Banda Aceh, Aceh, Indonesia is undernutrition and overnutrition, cases of undernutrition were more numerous than overweight and obesity, even though the number of malnutrition cases did not show any difference between men and women in all categories.